The Semantic Web : 6th International Semantic Web Conference, 2nd Asian Semantic Web Conference, ISWC 2007 + ASWC 2007, Busan, Korea, November 11-15, 2007 : proceedings - International Semantic Web Conference (6th : 2007 : Pusan, Korea); Aberer, Karl. (New York : Springer)
PSZJBL